INTERAKSI MASYARAKAT SEKITAR DENGAN KAWASAN CAGAR ALAM DAN CAGAR ALAM LAUT PANGANDARAN - Denni Susanto; Lies Rahayu Wijayanti Faida; Fahina Risqi Hidayana Lubis; Rizka Hanisaputra (Jurnal Belantara, 2020)
Communities and conservation areas are two things that cannot be Separated. Surrounding communities interact with conservation areas to fulfil their needs. This study aimed to know the forms of interaction between communities and the Nature Reserve and Marine Nature Reserve of Pangandaran as well as the factors that underlie these interactions. The method used in this study was a survey method with a total sample of 254 people. The target communities interviewed were communities of Pangandaran Village who carry out activities in Nature Reserve and Marine Nature Reserve of Pangandaran. The analysis used for data processing was descriptive analysis. The results showed that 44% of the community doing activities as fishermen, 17% renting out cruise ship services, 12% renting snorkeling equipment, 11% doing fishing activities, 6% as bagang fishermen and tour guides, and 4% as fishing fishermen. Factors underlying the interaction in Nature Reserve and Marine Nature Reserve of Pangandaran were community economic factors.